Connecting - Helen Walker; Bob Randolph; Leigh Ann Chow; Andrea Saylor; Jill Moyer Sunday; Kattie Hogan; Matt Ittig; John Patrick Cleary (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Connecting Helen Walker - Gratitude Bob Randolph - Poetry Teacher's Prayer Leigh Ann Chow - What Teachers Carry Andrea Saylor - A Brief History of Holy Writing Jill Moyer Sunday - For My Students Kattie Hogan & Matt Ittig - Lines on the Body: Confronting Personal Experiences through Poetry John Patrick Cleary - New Teacher